LOGÍSTICA VERDE Y GESTIÓN AMBIENTAL: DESAFÍO PARA EL GOBIERNO CORPORATIVO EN LAS ORGANIZACIONES LUCRATIVAS - Raysa, Dra. Chirino García, (IJRDO - Journal of Social Science and Humanities Research, 2018)
The purpose of this study was to generate reflections on the use and implementation of green logistics and environmental management, since there is the problem caused by the lack of interest that corporate governance confers on these variables, since the processes in addition to the practices that are carried out by the for-profit organizations along the value chain and supplies are loaded with anthropic activities that constitute a threat to the environment as well as to the quality of life of future generations, under the legal precepts of the Venezuelan legal system together with the theoretical postulates of Chirino (2015), Días (2004), Embum and Zuleta (2001), Latorre (2000), Zhang (2010). The investigation was typified as documentary, descriptive, led to the consideration of the environmental problem product of the intense business activity, which generates a progressive deterioration of the environment. It was concluded that in order to implement an efficient and effective system of green logistics and environmental management, a total mentalization and cooperation must be produced among all the actors involved in a productive process, such as: State, supplier, human capital, distribution, transport and user. final because every day the demand for goods and services is greater; Therefore, the application of the 5 Rs of logistics is ineludible, as well as the creation of an operator, who will be responsible for these aspects to contribute to clean and healthy activities.